Phenotypic and Molecular Characterization of Rice Genotypes’ Tolerance to Cold Stress at the Seedling Stage - Nasira Akter (Sustainability, 2022)
Rice plants are affected by low-temperature stress during germination, vegetative growth, and reproductive stages. Thirty-nine rice genotypes including 36 near-isogenic lines (NILs) of BRRI dhan29 were evaluated to investigate the level of cold tolerance under artificially induced low temperature at the seedling stage. Three cold-related traits, leaf discolouration (LD), survivability, and recovery rate, were measured to determine the level of cold tolerance. Highly significant variation among the genotypes was observed for LD, survivability, and recovery rate. Three NILs, IR90688-74-1-1-1-1-1, IR90688-81-1-1-1-1-1, and IR90688-103-1-1-1-1-1, showed tolerance in all three traits, while IR90688-118-1-1-1-1-1 showed cold tolerance with LD and recovery rate. IR90688-92-1-1-1-1-1, IR90688-125-1-1-1-1-1, IR90688-104-1-1-1-1-1, IR90688-124-1-1-1-1-P2, IR90688-15-1-1-1-1-1, and IR90688-27-1-1-1-1-1 showed significantly higher yield coupled with short growth duration and good grain quality. Genetic analysis with SSRs markers revealed that the high-yielding NILs were genetically 67% similar to BRRI dhan28 and possessed cold tolerance at the seedling stage. These cold-tolerant NILs could be used as potential resources to broaden the genetic base of the breeding germplasm to develop high-yielding cold-tolerant rice varieties.